Evidence That the Variable Regions of the Central Domain of VlsE Are Antigenic during Infection with Lyme Disease Spirochetes - McDowell, John V. (American Society for Microbiology, 2002)
It has been postulated that the vls system of the Lyme disease spirochetes contributes to immune evasion through antigenic variation. While it is clear that vlsE undergoes sequence change within its variable regions at a high frequency during the early stages of infection, a definitive role in immune evasion has not been demonstrated. In this report we assessed the murine and human humoral immune response to recombinant (r)-VlsE variants that originally arose during infection in mice. Immunoblot analyses of r-VlsE variants were conducted by using serum samples collected from mice infected with Borrelia burgdorferi clones that carried different vlsE variants. All of the r-VlsE variants were recognized by infection sera regardless of the identity of the infecting clone or isolate. In addition, all variants were immunoreactive with a panel of human Lyme disease patient serum samples. It is evident from these analyses that the infection-induced VlsE variants share common epitopes that reside within conserved segments of these proteins. However, preabsorption experiments revealed that the variable regions of the central domain of VlsE, which undergo rapid mutation during infection, also influence the antigenic properties of the protein. A subset of the antibodies elicited against vlsE variants that differ in the sequences of their variable regions were found to be variant specific. Hence, in spite of a robust antibody response to conserved segments of VlsE, infection-induced sequence changes within the variable regions alter the antigenicity of VlsE. These results provide the first direct evidence of antigenic variation in the VlsE protein.